Genetic divergence analysis in basmati rice genotypes (Oryza sativa L.) for agro-morphological and quality traits using multivariate approach - Kumar, Vinod; Singh, Dhirendra (ORYZA-An International Journal of Rice, 2021)
Genetic diversity of 30 basmati rice genotypes was analysed based on nine agro-morphological and six quality traits. The results of the principal component analysis showed that the first six principal components explained 89.16% of the total variation in the experimental material. These 30 basmati genotypes were grouped into six clusters which indicated the presence of sufficient diversity among the tested genotypes. Cluster I and cluster III was found to be the largest comprising of 10 genotypes each followed by cluster II having seven genotypes. The highest average intra-cluster distance was observed in cluster III. Highest inter-cluster distance (D2) was observed between clusters III and VI followed by clusters III and V, III and IV & clusters II and III. Cluster IIshowed high mean value for grain yield per plant, 1000 grain weight, and grain length. The characters viz., amylose content, grain length after cooking, spikelet per panicle, grain width, grain length and 1000 grain weight contributed maximum towards total genetic divergence, suggest their suitability of selection.